Citizen science reveals alarming update on the invasion of the Asian mantleslug Meghimatium pictum in Brazil - Rafael M. Rosa; Daniel C. Cavallari; Marcel S. Miranda; Fernanda S. Silva; Rodrigo B. Salvador (PLoS ONE, 2025)
The Asian mantleslug Meghimatium pictum is an exotic species introduced to Brazil in the late 1990s, but only formally reported in 2011. Since then, it has been deemed an agricultural pest and given the status of an invasive species; furthermore, it has been confirmed as an intermediate host for the nematode Angiostrongylus costaricensis in Brazil. Despite its potential for impacts, no additional studies on the status of its invasion have been conducted since the initial report. In this study, we used the citizen science platform iNaturalist to analyse the current distribution of M. pictum in Brazil, while also using genetic barcode data to understand the relationships between Brazilian and Asian populations and applying a species distribution model to investigate the suitable range for its distribution in Brazil. Our survey has recovered a total of 520 new records of this species in Brazil, confirming its spread to four additional states since its original report. Currently, M. pictum is recorded in the Distrito Federal and the states of Minas Gerais, Espírito Santo, Rio de Janeiro, São Paulo, Paraná, Santa Catarina, and Rio Grande do Sul. Our phylogenetic analysis suggests a close relationship between M. pictum populations in South America and those from Okinawa, Taiwan, and Guangzhou (mainland China), the latter being the most likely point of origin for the South American populations. Our species distribution model supports the idea that, in Brazil, the species is largely restricted to subtropical areas belonging to the Atlantic Forest ecoregion, while also showing suitable areas where the species has not been recorded yet and might become established in the near future. The implications of these findings are discussed, highlighting the recent surge in records and the usefulness of iNaturalist as a tool to monitor invasive species in the country.